Dronitaly the event for Unmanned Vehicle System in Milan - De Fabritiis, Fabrizio (GEOmedia, 2015)
Dronitaly is the event dedicated to all Unmanned Vehicle Systems (aerial, aquatic or land) that unites the leading names in professional remotely piloted systems market: producers, distributors, aeronautical operators, service providers, flying schools, universities, institutions, regulatory authorities, associations and the media.